Valorization of Seafood Processing Discards: Bioconversion and Bio-Refinery Approaches - Venugopal, V. (Frontiers in Sustainable Food Systems, 2021)
The seafood industry generates large volumes of wastes. These include processing discards consisting of shell, head, bones, intestine, fin, skin and others, and also low-value under-utilized fish, which are caught as by-catch of commercial fishing operations. In addition, fish processing generates voluminous amounts of wastewater as effluents. The discards, by-catch and effluents are rich in nutrients including proteins, amino acids, polyunsaturated fatty acids (PUFA) rich lipids, carotenoids, and minerals. The seafood wastes lead to losses of nutrients as well as serious environmental hazards. It is important that these wastes are treated by secondary processing to address the problems. Unlike most chemical processes biological treatments are environmental friendly, safe and cost-effective. These are based on bioconversions of components of the seafood waste into valuable ingredients, which are then recovered by green technologies. The bioconversion processes make use of microbial fermentations or direct actions of exogenously added enzymes. Recent developments in algal biotechnology offer novel processes for bioconversion of seafood components into algal biomass, which can be used as feedstock for the recovery of useful ingredients including biofuel. Integration of multiple processes into biorefinery have potentials for eco-friendly and cost-effective valorization of seafood wastes, which in turn can support sustainable seafood production and bioeconomy .